PENGEMBANGAN MEDIAVIDEO ANIMASI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE LEARNING PADA TEMA KEWAJIBAN DAN HAKKU KELAS III SD - Pransiska1, Rindi; Silalahi, Beta Rapita; Surya, Muhammad Kafi (Universitas Negeri Semarang, 2023)
This research is a type of development research (research and development) with reference to the 4D model which is an extension of Define, Design, Development and Dissemination. The instrument used to collect data is a questionnaire. The data analysis technique is descriptive qualitative. The results of the research on the teacher's response to the media obtained a percentage of 93%. This percentage includes very valid criteria (very feasible) to be used as learning media for grade III elementary school students on the theme of My Obligations and Rights. The overall assessment of the media expert review received a percentage of 98%. This percentage includes very valid criteria (very feasible) to be used as media in learning activities for grade III elementary school students on the theme of My Obligations and Rights. The overall assessment of the material expert review received a percentage of 86%. This percentage includes valid criteria (feasible) to be used as media in learning activities for grade III elementary school students on the theme of My Obligations and Rights